2014
DOI: 10.1038/ncomms6773
|View full text |Cite
|
Sign up to set email alerts
|

A fully atomistic computer simulation study of cold denaturation of a β-hairpin

Abstract: Cold denaturation is a fundamental phenomenon in aqueous solutions where the native structure of proteins disrupts on cooling. Understanding this process in molecular details can provide a new insight into the detailed natures of hydrophobic forces governing the stability of proteins in water. We show that the cold-denaturation-like phenomenon can be directly observed at low temperatures using a fully atomistic molecular dynamics simulation method. Using a highly optimized protein force field in conjunction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 39 publications
5
48
1
Order By: Relevance
“…The most pronounced decrease is observed at W6, G11, and P18-nonpolar residues that are part of Trp-cage's hydrophobic core. This behavior is consistent with the viewpoint that cold unfolding is accompanied by the hydration of buried nonpolar residues, leading to a reduction in their effective hydrophobicity at low temperatures (21,22,(24)(25)(26)43). Thus, hydrophobic hydration, though not the dominant effect energetically (at least not in Trp-cage), is responsible for A B the increase in the overall "hardness" of the protein-water interface upon cooling.…”
Section: Hydration Of Trp-cagesupporting
confidence: 75%
See 2 more Smart Citations
“…The most pronounced decrease is observed at W6, G11, and P18-nonpolar residues that are part of Trp-cage's hydrophobic core. This behavior is consistent with the viewpoint that cold unfolding is accompanied by the hydration of buried nonpolar residues, leading to a reduction in their effective hydrophobicity at low temperatures (21,22,(24)(25)(26)43). Thus, hydrophobic hydration, though not the dominant effect energetically (at least not in Trp-cage), is responsible for A B the increase in the overall "hardness" of the protein-water interface upon cooling.…”
Section: Hydration Of Trp-cagesupporting
confidence: 75%
“…Theoretical studies of coarse-grained models have suggested that the protein structure is destabilized during cold denaturation by the exposure of the buried hydrophobic groups to water (21,22,(24)(25)(26)43). Although our findings suggest that hydrophobic hydration is not the dominant driving force for cold unfolding, we investigated this process further by computing the number of water molecules surrounding each residue (Fig.…”
Section: Hydration Of Trp-cagementioning
confidence: 99%
See 1 more Smart Citation
“…At every exchange interval, 32768 ( N3, where N=32 is the number of replicas) random exchanges were attempted as suggested by Chodera and Shirts . Virtual sites were used for all protein hydrogens which permitted a time step of 4 fs to be used, a strategy that has been successfully employed before . Protein bonds were constrained using the P‐Lincs algorithm with an expansion order of 6 and water molecules were constrained with the Settle algorithm .…”
Section: Methodsmentioning
confidence: 99%
“…However, the interpretations of the mechanism are still controversial [8,[24][25][26][27][28][29][30][31][32][33][34][35][36][37]. High-T denaturation is easily understood in terms of thermal fluctuations that disrupt the compact protein conformation: the open protein structure increases the entropy S minimizing the global Gibbs free energy G ≡ H − TS, where H is the total enthalpy.…”
mentioning
confidence: 99%